NYMPHSTAR: an accurate high-throughput quantitative method for whitefly (Aleurotrachelus socialis Bondar) resistance phenotyping in cassava - Bohorquez-Chaux, Adriana; Gómez Jiménez, Maria Isabel; Becerra López Lavelle, Luis Augusto; Leiva Sandoval, Luisa Fernanda (Wiley, 2023)
Whitefly (Aleurotrachelus socialis Bondar) is an important pest causing high economic losses in cassava production systems in the north of South America. It reduces the plant’s photosynthesis by colonizing the cassava leaves and either directly feeding on their phloem sap or excreting substances that allow the growth of sooty mold and the consequent reduction of the photosynthetic area. The deployment of the crop’s natural resistance to this pest is the most effective approach to its management. Phenotypic evaluation to identify germplasm with superior whitefly-resistance (WFR) levels from that showing a whitefly susceptible (WFS) response will benefit from the availability of an accurate high-throughput, quantitative phenotyping method.